HERBAL REMEDIES OF AQUATIC MACROPHYTES OF GORAKHPUR DISTRICT, UTTAR PRADESH (INDIA) - ALKA GUPTA,; V. N. PANDEY, (International Journal of Pharma and Bio Sciences, 2014)
Uttar Pradesh is situated in north central part of India and district Gorakhpur is situated in the Northern Terai Region of U.P. (India) below the lofty Himalayan Mountain. The climate and water bodies of this region provide best habitat for the luxuriant growth of aquatic macrophytes. Aquatic plants are miraculous green plants having multifarious potential for food, fodder, medicine and various ailments and diseases. Aquatic plants are used by people since ancient times as source of their day to day requirements due to the presence of different nutrient and chemical constituents. Therefore attempt has been made to document some of the known medicinal properties of aquatic plants which are used to cure various diseases.